Validation of Turkish version of Eastern Cooperative Oncology Group Performance Status (ECOG-PS) for gynecologic oncology patients - Api, Murat; Purut, Yunus Emre; Akış, Serkan; Keleş, Erhan; Ceylan, Yasemin; Kabaca Kocakuşak, Canan; Giray, Burcu; Güray Uzun, Mine (BMJ Publishing Group, 2019)
[Abstract Not Available]
Keywords: Eastern Cooperative Oncology Group Performance Status (ECOG-PS); Gynecologic Oncology Patients; Turkish Version